Kontestasi antara Muslim Fundamentalis dan Muslim Liberal dalam Perebutan Makna Sosial Keagamaan di Indonesia - Nur Hidayat Wakhid Udin (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2018)
Islam is a religion that highly respects and appreci-ates the values of humanity and puts strong emphasis on the creation of peace and harmony among humankind. It rejects and even condemns violent actions in any form with any means. However, the facts show us that ideological and political contestation, among the existed groups in Islam, often lead to open conflict, as can be observed in several cases. The article attempts to portray the contestation of Islamic Fundamentalist group and Islamic Liberal group in Indonesia. Although there have been many studies conducted and published on this issue, I see yet the importance of discussion about the issue. The significance could be observed in the fact that it is one of socio-religious problems faced by the Muslim community around the world, including Indonesia. Employing descriptive-qualitative approach the study stresses that different perspectives used and dissimilarly opposite interpretation produced by each group in understanding and interpreting the religious texts have resulted in massively deep but even hot contestation between the two groups. While the Islamic Fundamentalist group tends to see the holy texts in their narrow and rigid understanding, the Islamic Liberal one understands the texts loosely and, to a lesser extent, unrestrained.